Distribuição espacial dos casos de covid-19 no início da pandemia na cidade de araguaina-to 2020 - 2021. - SILVA, Clara Davis Carneiro da (Universidade Federal do Tocantins, 2023)
The objective of this work is to understand how the COVID-19 pandemic reached the population in Araguaína - TO in 2020 and 2021. However, to obtain the results, data available in the bulletins of the state and municipal health departments were used, Tabnet-Datasus. Coronavirus causes respiratory infections. Also known as COVID-19 (nCoV-2019) it was discovered on 12/31/19 after the first cases registered in China, and consequently for the municipalities. (For the world) The spatial cutout is the city of Araguaína – TO and the temporal cutout is the year 2020. In Araguaína, 16,741 cases were confirmed until 11/30/2020, and 235 evolved to death. A quantitative-qualitative research was developed, with a bibliographic reference of publications from SciELO, BIREME, PAHO/WHO, among other productions. The Covid-19 data (maps, epidemiological bulletins) are available on the website of the Municipality of Araguaína. From geographical science, and the search for interdisciplinary understanding, the research showed through spatial analysis, where there were more occurrences of the disease, found preventive actions, but it was not possible to contain the spread of the disease due to the complexity and politicization of pandemic that implies in hindering and minimizing this situation. Another factor is the population behavior itself and the low incidence of immunization applications. The vaccine is primarily reaching the age groups considered priority, which are the elderly, adults with comorbidities, pregnant women, health professionals, sanitation and public safety. The number of new cases of the disease began to fall, bringing a feeling of relief. However, the immunization capacity of the vaccine still does not reach 100%.